ASSOCIATION BETWEEN INFANT FORMULA AND PACIFIER SUPPLY IN MATERNITY AND BREASTFEEDING IN THE FIRST SIX MONTHS OF LIFE - Osvaldinete Lopes de Oliveira Silva; Marina Ferreira Rea; Flávia Mori Sarti; Milene de Oliveira Silva (Universidade do Estado do Rio de Janeiro, 2019)
Introduction: Breastfeeding (BF) provides the basis for health, food and nutrition supply. It should be promoted at the maternity hospital through practices such as the 6th step (avoid any food or fluid supplements) and 9th step (avoid feeding bottles, teats and pacifiers) of the Baby-Friendly Hospital Initiative (BFHI). Purpose: To assess the compliance with BFHI steps 6 and 9 among patients in public hospitals and its association with BF in the first six months of life. Methodology: Prospective cohort of patients enrolled in six hospitals in Sao Paulo municipality (three Baby-Friendly Hospitals, BFHs, and three non-BFHs). Mothers were interviewed at maternity ward, and by phone 30 and 180 days after child birth. Compliance with steps 6 and 9 of BFHI, and BF practices were investigated. Associations were analyzed through logistic regression adjusted for confounding variables, determined by the directed acyclic graph (DAG). Results: Sample comprised of 969 mothers in the first interview, 902 in the second and 814 in the third with steps 6 and 9 observed in both groups. Non-compliance of step 6 reduced exclusive breastfeeding (EBF) at 30 days (aOR=1.82; CI=1.19-2.77) and at 180 days (aOR=1.79; CI=1.15-2.78). Non-compliance of step 9 reduced EBF at 30 days (aOR=2.33, CI=1.30-4.19). Conclusion: The possibility of EBF in the first month of life was reduced by the offer of infant formula and pacifier in the maternity ward. At six months, breastfeeding was reduced by the introduction of infant formula in the maternity ward. The results emphasize the importance of complying with the International Code of Marketing of Breastmilk Substitutes, providing a safe environment that encourages women to choose to breastfeed. DOI: 10.12957/demetra.2019.43555